THE USE OF LORAKSON FOR THE TREATMENT OF DOGS WITH PNEUMONIA - Кравченко, С. О. (Scientific Progress & Innovations, 2013)
Research has found that the use of antibiotics “Lorakson” to treat pneumonia in dogs is accompanied by normalization of the clinical condition of sick animals and some morphological and biochemical parameters of blood. After injection of “Lorakson” intramuscularly at a dose of 30 mg / kg twice a day for 7 days the general condition of sick dogs improves, appetite reduces and fever disappeares on the second day. The number of leukocytes decreases to the limits of the parameters of the clinically healthy animals, rates of protein metabolism, namely content of general protein and globulin particles, on the seventh day normalizes.